2020
DOI: 10.1111/acel.13267
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonists delay age‐associated metabolic disease and extend longevity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…Our results showed that the protective effect of LXA4 was reversed by GW9662, indicating that LXA4 exerts its renal protection by binding to PPAR-g. As the main function of PPAR during the inflammatory reaction is to promote the inactivation of NF-kB (23), and NF-kB signaling was also implicated in cellular senescence via the ROS-NF-kB-p53 pathway (33), we further determined the expression of the NF-kB-p53-p21 senescent pathway in the kidney sections and found that the pathway was activated in the CLP model, and the changes were reversed by the PPAR-g antagonist GW9662. These results are consistent with a recent study showing that PPAR-g agonists delays cellular senescence and age-associated metabolic disease (34). All the results indicate that LXA4 exerts its anti-senescence and antiinflammatory effects via the PPAR-g/NF-kB pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the protective effect of LXA4 was reversed by GW9662, indicating that LXA4 exerts its renal protection by binding to PPAR-g. As the main function of PPAR during the inflammatory reaction is to promote the inactivation of NF-kB (23), and NF-kB signaling was also implicated in cellular senescence via the ROS-NF-kB-p53 pathway (33), we further determined the expression of the NF-kB-p53-p21 senescent pathway in the kidney sections and found that the pathway was activated in the CLP model, and the changes were reversed by the PPAR-g antagonist GW9662. These results are consistent with a recent study showing that PPAR-g agonists delays cellular senescence and age-associated metabolic disease (34). All the results indicate that LXA4 exerts its anti-senescence and antiinflammatory effects via the PPAR-g/NF-kB pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have provided reliable clinical evidence, suggesting that insulin resistance is a major cardiovascular risk factor independent of other risk factors in CVDs in older adults in community populations and patients with type I and type II diabetes ( 79 ). In patients with ischemic stroke, insulin resistance is independently associated with poor functional prognosis after acute ischemic stroke ( 80 , 81 ). Skeletal muscle is the leading site of glucose uptake, deposition, and actin secretion, which protect insulin resistance.…”
Section: The Pathogenesis Of Sarcopenia and Cvdsmentioning
confidence: 99%
“…Transient receptor potential vanilloid 1 (TRPV1), which is also a target of anandamide, has been recently implicated in the expression of LTP at hippocampal CA1 region [ 24 ]. Thus, we evaluated if TRPV1 antagonism with a specific drug (AMG9810) might reverse the beneficial effect on synaptic plasticity observed in 5xFAD FAAH-null mice.…”
Section: Resultsmentioning
confidence: 99%